Secure Collision-Free Frequency Hopping for OFDMA-Based Wireless Networks. (20th August 2009) - Lightfoot, Leonard; Zhang, Lei; Ren, Jian; Li, Tongtong
Abstract : This paper considers highly efficient antijamming system design using secure dynamic spectrum access control. First, we propose a collision-free frequency hopping (CFFH) system based on the OFDMA framework and an innovative secure subcarrier assignment scheme. The CFFH system is designed to ensure that each user hops to a new set of subcarriers in a pseudorandom manner at the beginning of each hopping period, and different users always transmit on nonoverlapping sets of subcarriers. The CFFH scheme can effectively mitigate the jamming interference, including both random jamming and follower jamming. Moreover, it has the same high spectral efficiency as that of the OFDM system and can relax the complex frequency synchronization problem suffered by conventional FH. Second, we enhance the antijamming property of CFFH by incorporating the space-time coding (STC) scheme. The enhanced system is referred to as STC-CFFH. Our analysis indicates that the combination of space-time coding and CFFH is particularly powerful in eliminating channel interference and hostile jamming interference, especially random jamming. Simulation examples are provided to illustrate the performance of the proposed schemes. The proposed scheme provides a promising solution for secure and efficient spectrum sharing among different users and services in cognitive networks.